The Hobbit hyperreality paradox : Polarization among audiences for a 3D high frame rate film - Michelle, Carolyn and Davis, Charles H and Hight, Craig and Hardy, Ann L (Convergence: The International Journal of Research into New Media Technologies, 2017)
The 3D high frame rate version of Peter Jackson’s first Hobbit film was touted as offering one of the most realistic and engaging movie-going experiences to date, its innovative projection technologies promising to greatly enhance viewers’ sense of immersion in the fantastical world of Middle-earth. However, our empirical research suggests the specific combination of technologies in The Hobbit had paradoxical perceptual and experiential effects. Whereas the groundbreaking hyperrealistic aesthetic enhanced both spectacular and narrative immersion for many viewers, a significant number experienced this same visual aesthetic as unconvincing and distracting and as undermining suspension of disbelief. In this article, we identify key factors contributing to polarization among Hobbit viewers on aesthetic grounds and offer empirical insights into how emerging cinematic technologies may be reshaping film spectatorship.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTE1NTg0ODgw